LABOR RIGHTS IN THE NEWLY REVISED CONSTITUTION - A. Yakubov (Web of Journals Publishing, 2024)
This article analyzes the main aspects of labor rights and their implementation in the newly revised Constitution. The significance of new provisions regarding the right to work, employment, workplace safety, fair wages, rest, and social protection is outlined in the Constitution.
Keywords: newly revised Constitution, employment, labor protection, fair wages, social protection, state guarantees, citizens' rights, workers' interests.